2017
DOI: 10.1016/j.molcel.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation of C9orf72 Dipeptide Repeats Perturbs Stress Granule Dynamics

Abstract: SummaryLiquid-liquid phase separation (LLPS) of RNA-binding proteins plays an important role in the formation of multiple membrane-less organelles involved in RNA metabolism, including stress granules. Defects in stress granule homeostasis constitute a cornerstone of ALS/FTLD pathogenesis. Polar residues (tyrosine and glutamine) have been previously demonstrated to be critical for phase separation of ALS-linked stress granule proteins. We now identify an active role for arginine-rich domains in these phase sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
561
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(595 citation statements)
references
References 64 publications
34
561
0
Order By: Relevance
“…Molecular crowding affects phase separation and RNA granule assembly both in vitro and in cells (Boeynaems et al, 2017; Bounedjah et al, 2012; Kedersha et al, 2016; Molliex et al, 2015). The molecular crowding agent Ficoll causes a ten-fold reduction in r(G4C2)4 and b-isox required to promote condensation (Fig 4E, lanes 2, 6, 10, 13, 17).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular crowding affects phase separation and RNA granule assembly both in vitro and in cells (Boeynaems et al, 2017; Bounedjah et al, 2012; Kedersha et al, 2016; Molliex et al, 2015). The molecular crowding agent Ficoll causes a ten-fold reduction in r(G4C2)4 and b-isox required to promote condensation (Fig 4E, lanes 2, 6, 10, 13, 17).…”
Section: Resultsmentioning
confidence: 99%
“…The range of sequence biases associated with IDRs that mediate phase separation indicates that there may be a range of underlying driving forces. These likely include electrostatic, dipole–dipole, pi–pi, cation–pi, hydrophobic, and hydrogen bonding interactions [9,49,50,5256] (Figure 2A,B). Indeed, mutational studies have demonstrated that phase separation of different LCDs can be prevented by interfering with a variety of residue types [9,10,14,16,57].…”
Section: Molecular Determinants Of Protein Phase Separation In Vitromentioning
confidence: 99%
“…A growing understanding of the underlying molecular principles and the physicochemical forces that drive the formation of membraneless organelles (see Glossary) has enabled the elucidation of their diverse functions in a variety of cellular processes, including the stress response, the regulation of gene expression, and the control of signal transduction [58]. In the past few years, there has been increasing evidence for the involvement of membraneless organelles in age-related disorders, such as amyotrophic lateral sclerosis (ALS) [916]. Together, these discoveries have created a new field in cell biology, focused on understanding how organization of cellular matter into membraneless organelles contributes to function, and how their dysregulation leads to disease.…”
Section: Introductionmentioning
confidence: 99%
“…This propensity has been localised to a low-complexity domain in the C-terminal region that may play a role in RNA binding, granule formation, and/or liquid–liquid phase separation to subserve transcription dynamics and mRNA transport [6, 12, 32, 34, 55, 56]. It is hypothesised that inherited or spontaneous mutation of the encoding gene, TARDBP , or of an interacting partner, upsets the balance between aggregation and dissolution of TDP-43 [14, 71], which may be differentially regulated under changing conditions, including during the cellular stress/death response [7, 30]. …”
Section: Introductionmentioning
confidence: 99%